2014
DOI: 10.1242/bio.20146312
|View full text |Cite
|
Sign up to set email alerts
|

Distinct adaptor proteins assist exit of Kre2-family proteins from the yeast ER

Abstract: The Svp26 protein of S. cerevisiae is an ER- and Golgi-localized integral membrane protein with 4 potential membrane-spanning domains. It functions as an adaptor protein that facilitates the ER exit of Ktr3, a mannosyltransferase required for biosynthesis of O-linked oligosaccharides, and the ER exit of Mnn2 and Mnn5, mannosyltransferases, which participate in the biosynthesis of N-linked oligosaccharides. Ktr3 belongs to the Kre2 family, which consists of 9 members of type-II membrane proteins sharing sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 39 publications
4
13
0
Order By: Relevance
“…Localization of Mnn6-myc was also observed by indirect immunofluorescent microscopy. Mnn6-myc showed an image of ER-localized proteins, both in the wild-type and Δsvp26 cells, which is consistent with our previous result shown by sucrose density fractionation (Noda et al, 2014).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Localization of Mnn6-myc was also observed by indirect immunofluorescent microscopy. Mnn6-myc showed an image of ER-localized proteins, both in the wild-type and Δsvp26 cells, which is consistent with our previous result shown by sucrose density fractionation (Noda et al, 2014).…”
Section: Resultssupporting
confidence: 91%
“…Deletion of either the SVP26 gene or the MNN6 gene leads to the accumulation of Mnn4 in the ER Mnn6 belongs to the Kre2 family proteins, and, unlike other members of the Kre2 family which localize to the Golgi, probably localizes to the ER as previously suggested 5 by our sucrose density fractionation experiment (Noda et al, 2014). It has been shown that in addition to Mnn6, Mnn4, which is probably also a type II membrane protein, is required for mannosyl phosphate transfer to the glycans (Odani et al, 1996).…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations